Emerging drugs for the treatment of angina pectoris. (1st October 2016) - Chong, Cher-Rin; Ong, Gao J; Horowitz, John D
ABSTRACT: Introduction: Angina pectoris, or symptomatic myocardial ischaemia, reflects an impairment of coronary blood flow, and usually a deficiency of available myocardial energetics. Treatment options vary with the precise cause, which may vary with regards to the roles of increased myocardial oxygen demand versus reduced supply. Traditionally, organic nitrates, β-adrenoceptor antagonists, and non-dihydropyridine calcium antagonists were the only commonly used prophylactic anti-anginal agents. However, many patients failed to respond adequately to such therapy, and/or were unsuitable for their use. Areas covered: A number of 'new' agents have been shown to represent ancillary forms of prophylactic anti-anginal therapy and are particularly useful in patients who are relatively unsuitable for either percutaneous or surgical revascularisation. These include modulators of myocardial metabolic efficiency, such as perhexiline, trimetazidine and ranolazine, as well as high dose allopurinol, nicorandil and ivabradine. The advantages and disadvantages of these various agents are summarized. Expert opinion: 'Optimal' medical treatment of angina pectoris now includes use of agents primarily intended to reduce risk of infarction (e.g. statins, aspirin, ACE inhibitors). In patients whose angina persists despite the use of 'standard' anti-anginal therapy, and who are not ideal for invasive revascularization options, a number of emerging drugs offer prospects of symptomatic relief.